2016
DOI: 10.1186/s13014-016-0635-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of DCs/CIKs combined with thoracic radiotherapy for patients with locally advanced or metastatic non-small-cell lung cancer

Abstract: BackgroundThe combination of dendritic cells (DCs) and cytokine-induced killer cells (CIKs) can induce the anti-tumor immune response and radiotherapy may promote the activity. We aimed to explore the feasibility of DCs/CIKs combined with thoracic radiotherapy (TRT) for patients with locally advanced or metastatic non-small-cell lung cancer (NSCLC).MethodIn this study, patients with unresectable stage III/IV NSCLC and an Eastern Cooperative Oncology Group performance status (ECOG PS) of 0–2 and previously rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
(32 reference statements)
1
19
0
1
Order By: Relevance
“…Our study showed that cisplatin treatment did not downregulate phenotypic expression even at higher concentration. Further, the percentage of HLADR was slightly increased in cisplatin treated cultures compared to untreated cells which are in line with the results reported earlier [40], that showed an increase in the expression of HLA class II upon treatment of dendritic cells with paclitaxel [38]. In a different study, it was reported that addition of cisplatin during DC differentiation did not inhibit T cell proliferation [41].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study showed that cisplatin treatment did not downregulate phenotypic expression even at higher concentration. Further, the percentage of HLADR was slightly increased in cisplatin treated cultures compared to untreated cells which are in line with the results reported earlier [40], that showed an increase in the expression of HLA class II upon treatment of dendritic cells with paclitaxel [38]. In a different study, it was reported that addition of cisplatin during DC differentiation did not inhibit T cell proliferation [41].…”
Section: Discussionsupporting
confidence: 89%
“…A clinical trial conducted in pancreatic cancer patients treated with a combinatorial treatment using the Onivyde and leucovorin /5FU regimen followed by 6 doses of autologous dendritic cell vaccine showing a substantial decrease in the tumour burden [36]. In addition, studies also showed a reduction in Treg/MDSC cells along with tumour speci c CD4 + and CD8 + T cell generation in patients when dendritic cell vaccines were combined with chemotherapeutic regimen [37][38][39]. In this context we studied the effect of cisplatin on SPAG9 primed DCs and the responding immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…1) involved autologous DCs exposed to autologous tumor-derived RNA, 196 tumor-cell lysates, [197][198][199][200][201][202][203] autologous tumor stem cell lysates, 204 self-renewing and proliferating autologous tumor cells, 205 allogeneic cancer cell line lysates, [206][207][208] TAAs or TAA-derived peptides [209][210][211][212][213][214][215][216][217][218] or a combination thereof. 219 Most clinical studies based on the latter approach preferred melanoma-associated differentiation antigens including premelanosome protein (PMEL; also known as gp100), antigens belonging to the melanoma antigen gene (MAGE) family, tyrosinase (TYR) and Melan-A (MLANA; also known as MART1) (Fig.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…230 Regarding the distribution across different cancer types ( Fig. 1), patients harboring melanoma were most commonly enrolled in these trials, 186,196,198,205,213,221,223,227,[231][232][233][234] followed by patients with prostate cancer, 206,208,212,215 glioma or glioblastoma (GBM), 185,197,202,219 hepatocellular carcinoma, 204,211,220 non-small cell lung carcinoma (NSCLC), 207,214,230 renal cell carcinoma (RCC), 201,203 esophageal carcinoma, 216,226 and pancreatic ductal adenocarcinoma, 209,217 among others. Of note, only two trials included a wide range of advanced solid tumors refractory to previous treatments.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…caused by chronic inflammation of synovial tissue. During the onset of RA, an acute inflammation of the synovial lining (synovitis) leads to an extensive expansion of the corresponding cells (i.e., pannus formation and inflammatory cytokines), massive infiltration of leukocytes of the innate immune system (i.e., T and B cells, plasmocytes, and macrophages), and synovial fibroblast proliferation (8)(9)(10). The latter are regarded as effector cells responsible for cartilage and bone destruction in RA.…”
Section: Discussionmentioning
confidence: 99%